Rowell Syndrome: A Comprehensive Review on Pathogenesis of a Rare and Challenging Entity and the Horizon of Targeted Therapeutics - Azadeh Khayyat; Seyed Amir Zohouri; Mohammad Ali Esmaaeil Pour; Parvaneh Hatami; Bruce R. Smoller (Health Science Reports)
ABSTRACT Background Rowell syndrome (RS), an infrequent illness characterized by a combination of erythema multiforme‐like manifestations and systemic lupus erythematosus, poses diagnostic and clinical issues to the healthcare system. Initially discovered by Dr. Virginie Rowell in 1963, the disorder manifests as an overlapping illness with various dermatological and rheumatological conditions, necessitating precise assessment. Method The review encompasses demographic characters, dermatological signs and symptoms, triggering or contributing factors, laboratory studies, diagnosis and therapy challenges, and the outcome of RS. Through an analysis of the literature, this study identifies sunlight, medication use, COVID‐19 vaccination, and bacterial infections as contributing predisposing risks. Laboratory abnormalities revealed positive antinuclear antibodies and rheumatoid factor as common features, supporting the autoimmune origin of this illness. Result Medications vary, with systemic corticosteroids used as the initial therapy, and appropriate proper outcomes are observed with rituximab and hydroxychloroquine. Recent discoveries in biological agents and targeted immunotherapies have provided useful options for personalized care. Conclusion In summary, our study provides detailed and valuable data to deepen our knowledge about RS, showing the need for further investigations to discover the mechanisms underlying its pathogenesis and to identify novel targeted agents that can individualize the treatment plan.